Palestine between Politics and Terror, 1945-1947 - Golani, Motti (Lebanon : Brandeis University Press, 2013)
A fascinating look at the end of British rule in Palestine, through the eyes of its final high commissioner.
Title Page; Contents; Preface; Abbreviations and Terms; Prologue: On the Road to Jerusalem; Part I | A Political Process as Though There Is NoTerrorism: November 1945-December 1946; 1 | The Only Chance for Palestine Is Partition; 2 | Toward a Clash with the Yishuv; 3 | Saving the Jews from Themselves: Operation Agatha; 4 | A State First, Immigration Later; Part II | To Fight Terrorismas Though There Is No Political Process: July 1946-August 1947; 5 | "The King David Hotel Crime"; 6 | The High Commissioner's "Conciliation Policy"; 7 | Martial Law; Epilogue; Bibliography; Index
Description based upon print version of record.
Keywords: Great Britain - Politics and government - 1936-1945.; Jewish-Arab relations - History - 1917-1948.; Jews - Palestine - Politics and government - 20th century; Mandates - Palestine; Palestine - History - 1929-1948.; Palestine - History - Partition, 1947.; Palestine - Politics and government - 1917-1948.; Terrorism - Palestine; Jews -- Palestine -- Politics and government -- 20th century; Mandates -- Palestine; Terrorism -- Palestine; Jewish-Arab relations -- History -- 1917-1948.; Palestine -- History -- 1929-1948.; Palestine -- Politics and government -- 1917-1948.; Great Britain -- Politics and government -- 1936-1945.; Palestine -- History -- Partition, 1947.; HISTORY / Middle East / Israel; Electronic books